Metal and Ligand Effect on the Structural Diversity of Divalent Coordination Polymers with Mixed Ligands: Evaluation for Photodegradation - Govindaraj, Manivannan; Zhong, Shih-Ying; Lin, Chia-Her; Chen, Jhy-Der (Molecules (Basel, Switzerland), 2023)
Eight coordination polymers constructed from divalent metal salts, N,N′-bis(pyridin-3-ylmethyl)terephthalamide (L), and various dicarboxylic acids are reported, affording [Co(L)(5-ter-IPA)(H2O)2]n (5-tert-H2IPA = 5-tert-butylisophthalic acid), 1, {[Co(L)(5-NO2-IPA)]⋅2H2O}n (5-NO2-H2IPA = 5-nitroisophthalic acid), 2, {[Co(L)0.5(5-NH2-IPA)]⋅MeOH}n (5-NH2-H2IPA = 5-aminoisophthalic acid), 3, {[Co(L)(MBA)]⋅2H2O}n (H2MBA = diphenylmethane-4,4′–dicarboxylic acid), 4, {[Co(L)(SDA)]⋅H2O}n (H2SDA = 4,4-sulfonyldibenzoic acid), 5, {[Co2(L)2(1,4-NDC)2(H2O)2]⋅5H2O}n (1,4-H2NDC = naphthalene-1,4-dicarboxylic acid), 6, {[Cd(L)(1,4-NDC)(H2O)]⋅2H2O}n, 7, and {[Zn2(L)2(1,4-NDC)2]⋅2H2O}n, 8, which were structurally characterized by using single-crystal X-ray diffraction. The structural types of 1–8 are subject to the metal and ligand identities, showing a 2D layer with the hcb, a 3D framework with the pcu, a 2D layer with the sql, a polycatenation of 2-fold interpenetrated 2D layer with the sql, a 2-fold interpenetrated 2D layer with the 2,6L1, a 3D framework with the cds, a 2D layer with the 2,4L1, and a 2D layer with the (102⋅12)(10)2(4⋅10⋅124)(4) topologies, respectively. The investigation on the photodegradation of methylene blue (MB) by using complexes 1–3 reveals that the degradation efficiency may increase with increasing surface areas.